SCIENCE TRAINING PROGRAM FOR HIGH ABILITY SECONDARY SCHOOL STUDENTS: THE DEVELOPMENT OF MAN, AN ENRICHMENT PROGRAM. - Keller, Dolores Elaine (Science Education, 1965)
The article offers information on the enrichment program that focuses on the natural science and science and was conducted to talented high school students of Fairleigh Dickinson University in Teaneck, New Jersey. The study indicated that gifted students have to be given the freedom of expression and individuality in such program to flourish their creativity and intellectual growth. The program was funded by the U.S. National Science Foundation. The students were exposed in activities involving psychology and biology laboratories.